2022
DOI: 10.3390/ijerph192013699
|View full text |Cite
|
Sign up to set email alerts
|

Physical Changes of Preschool Children during COVID-19 School Closures in Fujian, China

Abstract: The COVID-19 pandemic may constitute an “obesogenic lifestyle” that results in exacerbating childhood obesity. However, studies investigating regional sociodemographic factors including different age groups or sexes in children with obesity are lacking. We aimed to clarify the high obesity prevalence populations of preschool children to provide a regional basis for children’s health policy during the COVID-19 school closures. From May to September 2019, a total of 29,518 preschool children were included in a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
2
1
Order By: Relevance
“…In fact, the intra-pandemic restrictions and associated lifestyle changes seem to have affected our study population regardless of their specific age. Contrary to our study, although they also showed that preschool children gained extra weight during the COVID-19 pandemic, Li et al ( 27 ) stated that there was an increase in weight gain with increasing age among preschoolers in China. Unlike our study, they did not follow individual patients but compared given age groups through the years, which makes direct comparison rather difficult.…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, the intra-pandemic restrictions and associated lifestyle changes seem to have affected our study population regardless of their specific age. Contrary to our study, although they also showed that preschool children gained extra weight during the COVID-19 pandemic, Li et al ( 27 ) stated that there was an increase in weight gain with increasing age among preschoolers in China. Unlike our study, they did not follow individual patients but compared given age groups through the years, which makes direct comparison rather difficult.…”
Section: Discussioncontrasting
confidence: 99%
“…There have been numerous recent reports about childhood obesity rates during the COVID period. These reports have used various methods and have originated from various locations [ 7 , 8 , 10 , 13 , 14 , 17 ]. Two related reports about children treated in Kaiser Permanente of Southern California found increasing rates of overweight and obesity in that population during the COVID period.…”
Section: Discussionmentioning
confidence: 99%
“…Many aspects of COVID-19, especially lockdowns and quarantines, contributed to an obesogenic lifestyle, such as reduced opportunities for physical activity and changes in dietary patterns [7][8][9]. Reports from many nations and many settings have suggested that pediatric overweight and obesity did increase during the peak years for COVID-19, 2020 and 2021 [7][8][9][10][11][12][13][14][15][16][17][18][19]. However, many of these reports have used convenience samples.…”
Section: Introductionmentioning
confidence: 99%